Observations of the Cabibbo-Suppressed decays, and the Cabibbo-Favored decay *Supported in part by National Key R & D Program of China (2020YFA0406400, 2020YFA0406300); National Natural Science Foundation of China (NSFC) (11635010, 11735014, 11805086, 11835012, 11935015, 11935016, 11935018, 11975011, 11961141012, 12022510, 12025502, 12035009, 12035013, 12192260, 12192261, 12192262, 12192263, 12192264, 12192265); the Chinese Academy of Sciences (CAS) Large-Scale Scientific Facility Program; Joint Large-Scale Scientific Facility Funds of the NSFC and CAS (U1832207); the CAS Center for Excellence in Particle Physics (CCEPP); 100 Talents Program of CAS; Fundamental Research Funds for the Central Universities, Lanzhou University, University of Chinese Academy of Sciences; The Institute of Nuclear and Particle Physics (INPAC) and Shanghai Key Laboratory for Particle Physics and Cosmology; ERC (758462); German Research Foundation DFG (443159800), Collaborative Research Center CRC 1044, GRK 2149; Istituto Nazionale di Fisica Nucleare, Italy; Ministry of Development of Turkey (DPT2006K-120470); National Science and Technology fund; National Science Research and Innovation Fund (NSRF) via the Program Management Unit for Human Resources & Institutional Development, Research and Innovation (B16F640076; STFC) (United Kingdom); Suranaree University of Technology (SUT), Thailand Science Research and Innovation (TSRI), and National Science Research and Innovation Fund (NSRF) (160355); The Royal Society, UK (DH140054, DH160214); The Swedish Research Council; U. S. Department of Energy (DE-FG02-05ER41374). (1st February 2023) - Ablikim 麦, M. 迪娜; Achasov, M. N.; Adlarson, P.; Albrecht, M.; Aliberti, R.; Amoroso, A.; An 安, M. R. 美儒; An 安, Q. 琪; Bai 白, Y. 羽; Bakina, O.; Baldini Ferroli, R.; Balossino, I.; et al.
Abstract: Using electron-positron annihilation data samples corresponding to an integrated luminosity of 4.5 fb, collected by the BESIII detector in the energy region between and, we report the first observations of the Cabibbo-suppressed decays, , and the Cabibbo-favored decay with statistical significances of, , and, respectively. The branching fractions of these decays are measured to be %, %, and %, where the first uncertainties are statistical and the second are systematic. We find that the branching fraction of the decay is about one order of magnitude higher than that of .